Analysis Of Early Warning System In Cold Room Vaccine Storage With Iot System - Arniningtyas, Aprilina Gayuh; Pudji, Andjar; Yulianto, Endro; Ali, Latafat Mikayilzade (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Cold room as a cold room for vaccine storage is an environment with a controlled temperature used to maintainand distribute vaccines in optimal conditions. The results of this review are expected to be a reference for researchers andreaders with the development of research using the DS B1820 temperature sensor which will analyze the results of the datalogger output and linearity at sensitive locations Cold Room with LCD output and equipped with an IoT system web displayon a PC for monitoring and alarm and notification via telegram when there is a change in temperature approaching and outsidethe range of 2 - 8 ° C so that this can make it easier for officers to monitor the temperature and quality of the vaccine. In theresults of the study, temperature graphs and temperature data can be displayed which are recorded in minutes. Temperature measurement with standard tools produces the largest difference of 0.83. The lowest temperature was 2.06°C and the highest temperature was 8.31°C as well as telegram notification of early warning (2.58°C), evacuation vaccine (2.31°C), and exposed vaccine (8.6°C). With this research a Warning System was obtained which was achieved with telegram notifications namely early warning, evacuation vaccines and exposed vaccines to maintain vaccine quality.